Reproductive and health-related hazards of Lindane exposure in Aral sea area - Aru Balmagambetova; Ibrahim A Abdelazim; Gulmira Zhurabekova; Sapargali Rakhmanov; Yerbol Bekmukhambetov; Elnara K Ismagulova (Wolters Kluwer Medknow Publications, 2017)
Background: The Aral Sea problem arises after improper regulation of the water from cross-borders river and heavy application of the pesticides over the cotton fields in the area. Objectives: This review article was designed to highlight the reproductive and health-related hazards of Lindane exposure in Aral Sea area. Methods of Literature Research: PubMed search was done for the articles that have been published from January 2007 to December 2015 using the keywords; Lindane and related health hazards in human. Five articles were found and critically analyzed to highlight the reproductive and health-related hazards of Lindane exposure in Aral Sea area. Results: Men of reproductive age were exposed to organochlorine pesticides (including Lindane), which have estrogenic and antiandrogenic activity, and this exposure may affect the male reproductive health. The human maternal and cord blood levels of hexachlorocyclohexane (HCH) isomers, dichlorodiphenyldichloroethylene, and dichlorodiphenyltrichloroethane were higher in preterm labor than full-term labor cases. Exposure of the human farmers to Lindane may be associated with long-term abnormalities that affect sensory nerves, and short-term abnormalities that affect liver, with reduced hepatic enzymes activity and reduced hepatocyte RNA synthesis. The Lindane level of 61 ± 268 pg/g lipid detected in the newborns in Turkey. Recently; Lindane has been restricted in most countries since 2009 under the Stockholm Convention on Persistent Organic Pollutants. The WHOs International Agency for Research on Cancer reported that the large epidemiological studies in the United States and Canada showed a 60% increased risk of non-Hodgkin lymphoma in agricultural workers, and pesticide applicators exposed to Lindane. Conclusion: Organochlorine pesticides, including Lindane have estrogenic and antiandrogenic activity, which may affect the male reproductive health. The human maternal and cord blood levels of HCH were higher in preterm labor than full-term labor cases. Exposure of the human farmers to Lindane may be associated with long-term abnormalities that affect sensory nerves, and short-term abnormalities that affect liver. Further future studies needed, with screening program of blood levels of Lindane in people living in Aral Sea area to confirm the Lindane health-related hazards, and the use of Lindane should be restricted in the Aral Sea area, if such relation proved.